2019
DOI: 10.5296/ijch.v6i2.14923
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Leisure and Life Satisfaction: The Sample of University Students

Abstract: The aim of the study is to examine the meaning of leisure time and life satisfaction levels of university students in general and students studying in faculties of tourism and sports sciences specifically. The sample group was determined from Recreation and Recreation Management students in the faculties of Tourism and Sport Sciences of universities by using appropriate sampling method based on voluntariness. The study included a total of 1345 university students, 507 women (37.7%) and 838 men (62.3%). In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…However, the life satisfaction of the participants did not differ in terms of gender variable. This finding is similar to the literature (Er et al, 2019;Işık et al, 2014;Hintikka, 2001). Although Hyde's (2005) meta-analytical analysis of 124 studies examining the differences between women and men found small differences in terms of life satisfaction in terms of gender, most of the studies did not find a significant difference in the life satisfaction of both genders.…”
Section: Discussionsupporting
confidence: 88%
“…However, the life satisfaction of the participants did not differ in terms of gender variable. This finding is similar to the literature (Er et al, 2019;Işık et al, 2014;Hintikka, 2001). Although Hyde's (2005) meta-analytical analysis of 124 studies examining the differences between women and men found small differences in terms of life satisfaction in terms of gender, most of the studies did not find a significant difference in the life satisfaction of both genders.…”
Section: Discussionsupporting
confidence: 88%
“…In this regard, men had higher levels of life satisfaction than women. In the light of the literature findings, this did not overlap with the findings, Drakou et al [52], Er et al [6], Çakır and Harmandar Demirel, [53] and Soyer [54]. There was a positive and low-level relationship in the realization of a psychological experience sub-dimension and a negative and low-level relationship in the prevention of a worse condition and an improved condition sub-dimensions by age.…”
Section: Discussionsupporting
confidence: 57%
“…Harris [3] stated that leisure is characterized by freedom of choice, self-realization, and moods, such as pleasure and satisfaction [4]. The concept of leisure is also stated as a time period which individuals freely express themselves [5][6][7]. Iwasaki [8] suggested that benefit of leisure would contribute to leading a worthy and meaningful life and to increasing life quality [9].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, considering the increasing stress and living conditions, the positive effects of recreation on body and mental health will be better understood. Recreation, on the one hand, increases the physical movement of the individual and provides morale and motivation to the individual, on the other hand, socializes individuals by developing social relations (Er et al, 2019;Torkildsen, 1999).…”
Section: Introductionmentioning
confidence: 99%